2011
DOI: 10.1016/j.heares.2010.12.019
|View full text |Cite
|
Sign up to set email alerts
|

Cholinergic cells of the pontomesencephalic tegmentum: Connections with auditory structures from cochlear nucleus to cortex

Abstract: Acetylcholine (ACh) is a neuromodulator that is likely to play a role in plasticity as well as other phenomena at many sites in the auditory system. The auditory cortex receives cholinergic innervation from the basal forebrain, whereas the cochlea receives cholinergic innervation from the superior olivary complex. Much of the remainder of the auditory pathways receives innervation from the pedunculopontine and laterodorsal tegmental nuclei, two nuclei referred to collectively as the pontomesencephalic tegmentu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
67
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(69 citation statements)
references
References 117 publications
2
67
0
Order By: Relevance
“…In humans, auditory discrimination, signal detection in noise, and stimulus-counting tasks, for instance, have been reported to result in increased activation of the MOC system (e.g., Mishra and Lutman 2014;Smith et al 2012). The increase may be mediated by known descending projections: directly from inferior colliculus or auditory cortex to MOC neurons, or indirectly from auditory cortex to cochlear nucleus (Brown et al 2013b;Mellott et al 2011;Mulders et al 2000aMulders et al , 2000bSchofield et al 2011). These same pathways and mechanisms may be responsible for increasing MOC activity in tinnitus and low SLT.…”
Section: Discussionmentioning
confidence: 99%
“…In humans, auditory discrimination, signal detection in noise, and stimulus-counting tasks, for instance, have been reported to result in increased activation of the MOC system (e.g., Mishra and Lutman 2014;Smith et al 2012). The increase may be mediated by known descending projections: directly from inferior colliculus or auditory cortex to MOC neurons, or indirectly from auditory cortex to cochlear nucleus (Brown et al 2013b;Mellott et al 2011;Mulders et al 2000aMulders et al , 2000bSchofield et al 2011). These same pathways and mechanisms may be responsible for increasing MOC activity in tinnitus and low SLT.…”
Section: Discussionmentioning
confidence: 99%
“…The pedunculopontine nucleus (PPTg) and the laterodorsal tegmental nucleus are brainstem nuclei that collectively comprise the pontomesencephalic tegmentum (PMT), which provides cholinergic input to the MGB (Morley and Kemp, 1981;Woolf, 1991;Schofield et al, 2011). The PMT has been implicated in many systems responsible for wakefulness, sleep, and attention (Jones, 1991;Kozak et al, 2005;Boucetta et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The PMT has been implicated in many systems responsible for wakefulness, sleep, and attention (Jones, 1991;Kozak et al, 2005;Boucetta et al, 2014). In the context of the auditory system, PMT neurons are critical in sensory gating and detecting novel/difficult-to-identify signals through a number of direct and indirect descending circuits (Schofield et al, 2011). The AC is known to have direct axonal projections to the PMT cells themselves (Schofield et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was shown that descending projections from the inferior colliculus (Brown et al, 2013), the auditory cortex and even non-auditory brain areas (Brown et al, 2013) reach all the way down to the olivo-cochlear neurons in the superior olivary complex. Furthermore, there is a whole class of cholinergic neurons in a midbrain area called the ponto-mesencephalic tegmentum that is under cortical control and projects widely into every station of the auditory pathway, including the cochlear nucleus (Behrens et al, 2002;Schofield et al, 2011;Mellott et al, 2011). The latter comprise about 25 % of all cholinergic axons in the cochlear nucleus of rodents.…”
Section: Cholinergic Top-down Influence Of the Cortex On The Auditorymentioning
confidence: 99%